The effects of deep brain stimulation of the pedunculopontine nucleus on cognition in Parkinson's disease and Progressive Supranuclear Palsy. (2019) - Leimbach, Friederike; Gratwicke, James; Foltynie, Tom; Limousin, Patricia; Zrinzo, Ludvic; Jahanshahi, Marjan
Abstract: Deep brain stimulation (DBS) of the pedunculopontine nucleus (PPN) is a relatively new treatment approach for the axial symptoms of Parkinson's disease (PD) and Progressive Supranuclear Palsy (PSP). The results concerning the clinical benefits are variable and inconsistent. The effect of PPN-DBS on limited aspects of cognitive function has been examined in a handful of mainly single or multiple case studies. The aim of this study was to investigate the effects of PPN-DBS for PD and PSP using a comprehensive battery of neuropsychological assessment covering the main cognitive domains. Five patients with PD and two patients with PSP who were consecutively operated at our centre with PPN-DBS were administered a neuropsychological battery of cognitive tests within one month prior to surgery and one year after surgery. The majority of tests of cognition showed no significant change from before to after surgery. The only aspects of cognition that showed reliable decline in a proportion of the patients were some indices of processing speed (Stroop colour naming control task, WAIS-III digit symbol) and category switching verbal fluency. Despite the small and heterogeneous sample, the results indicate that PPN-DBS is generally safe from a cognitive perspective. Highlights: There was no significant change from before to one year after PPN-DBS surgery on the majority of tests of cognition in 5 patients with Parkinson's disease 2 patients with Progressive Supranuclear Palsy. The only reliable decline in a proportion of the patients was on some indices of processing speed and category switching verbal fluency. The results indicate that PPN-DBS is generally safe from a cognitive perspective.